2011
DOI: 10.1002/anie.201105415
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Catalyzed Domino Reactions

Abstract: While organocatalyzed domino reactions or "organocascade catalysis" developed into an important tool in synthetic chemistry during the past decade, the utility of N-heterocyclic carbenes (NHCs) as catalysts in domino reactions has only received growing attention in the past three years. Taking into account the unique activation modes of the substrates by NHC catalysts, it is often difficult to distinguish between a single chemical transformation and a sequential one-pot transformation. Therefore, herein we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
165
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 955 publications
(172 citation statements)
references
References 135 publications
1
165
0
6
Order By: Relevance
“…Extensive research has shown that chiral NHCs are a class of privileged chiral ligands for transition-metal catalysis 3,4 and that they are versatile chiral organocatalysts 5,6 that can generate one enantiomer preferentially in numerous organic transformations 7,8 . NHCs can catalyse chemical bond synthesis because of several unique chemical characteristics: they are strong s-donors 1 and good Brønsted bases, and they have moderate p-acidity 9 .…”
mentioning
confidence: 99%
“…Extensive research has shown that chiral NHCs are a class of privileged chiral ligands for transition-metal catalysis 3,4 and that they are versatile chiral organocatalysts 5,6 that can generate one enantiomer preferentially in numerous organic transformations 7,8 . NHCs can catalyse chemical bond synthesis because of several unique chemical characteristics: they are strong s-donors 1 and good Brønsted bases, and they have moderate p-acidity 9 .…”
mentioning
confidence: 99%
“…Numerous basic organocatalytic protocols for very efficient and highly stereoselective carbon-carbon and carbon-heteroatom bond formations are now part of the strategic arsenal of synthetic chemistry. 67,68 The Lipton group first reported the chiral diketopiperazine-catalyzed hydrocyanation of aldimines in 1996. 11 They investigated the stereoselective addition of HCN to a variety of imines catalyzed by synthetically obtained diketopiperazine-based organocatalyst 35 (Scheme 34).…”
Section: Enantioselective Strecker Reactions Using Organocatalystsmentioning
confidence: 99%
“…2,8 Cascade reactions catalyzed by N-heterocyclic carbenes (NHCs) have received attention due to the resulting rapid generation of complex products. 9 A few N-heterocyclic carbene catalyzed reactions have been reported to produce different indene or indane derivatives. For example, the cascade reactions of 2-formylcinnamates with imines, phthalaldehydes with imines, and phthalaldehydes with 3-aroylacrylates in the presence of NHC catalysts gave substituted indan-1-ones, 10a-c while NHC-catalyzed reaction of 3,3′-(1,2-phenylene)bis(1-phenylpropenones) with aldehydes produced 1,2,3-trisubstituted indanes.…”
Section: -(56-dichloroindan-1-yl)-1h-tetrazole (B) and 5-[(56-dichmentioning
confidence: 99%